2022
DOI: 10.3846/jbem.2022.16060
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts Between Parent Company and Non-Controlling Shareholders in Stakeholder-Oriented Corporate Governance: Evidence From Japan

Abstract: When a company establishes subsidiaries with capital provided by a third party, the subsidiaries’ shareholders include the parent company (controlling shareholders) and minority (noncontrolling) shareholders. When shareholders’ interests are divergent, conflicts may arise, causing inefficiencies in the management of the subsidiaries or the corporate group. Such conflicts among shareholders are called principal–principal (PP) conflicts. However, adopting stakeholder-oriented corporate governance, a practice pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Indeed, previous studies analyzing Japanese family firms, where stakeholder-oriented corporate governance is generally in practice, have shown that controlling shareholders in family firms are consistent with stewardship theory and that dividend payout ratios, profitability, and R&D expenditures are higher in family firms [47,48]. Further, previous studies investigating potential conflicts between parent and non-controlling shareholders in Japanese subsidiaries show that although dividends are reduced in subsidiaries, PP conflicts between parent and non-controlling shareholders are not severe, as the subsidiary's sales growth is promoted [21,22]. Moreover, information asymmetries between stakeholders and management are mostly resolved through insider communication [15].…”
Section: Concentrated Ownership and Audit Qualitymentioning
confidence: 75%
See 4 more Smart Citations
“…Indeed, previous studies analyzing Japanese family firms, where stakeholder-oriented corporate governance is generally in practice, have shown that controlling shareholders in family firms are consistent with stewardship theory and that dividend payout ratios, profitability, and R&D expenditures are higher in family firms [47,48]. Further, previous studies investigating potential conflicts between parent and non-controlling shareholders in Japanese subsidiaries show that although dividends are reduced in subsidiaries, PP conflicts between parent and non-controlling shareholders are not severe, as the subsidiary's sales growth is promoted [21,22]. Moreover, information asymmetries between stakeholders and management are mostly resolved through insider communication [15].…”
Section: Concentrated Ownership and Audit Qualitymentioning
confidence: 75%
“…Under these inter-firm networks, Japanese firms are monitored by banks and cross-holding companies in order to maintain strategic and long-term relationships. As a result, Japanese firms adopt so-called stakeholder-oriented corporate governance, which seeks to achieve goals beneficial to various stakeholders, including non-controlling shareholders [22,34,52,53]. Under stakeholder-oriented corporate governance, the demand for accounting information is small, as the interests among stakeholders are resolved through private channels [15].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations